The Use of Internet Rating Services to Reduce Information Asymmetry in the Trade Industry - Bennaton, John Patrick (2006)
George Akerlof introduced the concept of information asymmetry in his Nobel Prize winning paper The Market for Lemons, where he explained how problems of adverse selection can arise in markets that contain information asymmetry. Since then numerous academics have sought to explain how to overcome these problems, and have written various papers explaining how this could be done. Despite this there are still industries and markets that suffer from adverse selection problems due to information asymmetry. One such industry is the trade industry, where trade companies and professionals alike are increasingly being criticised for the quality of service that they provide, and for seeking excess profits due of the lack of consumer knowledge.